Challenges and Strategies in Prosecutorial Asset Tracing for Recovering State Losses from Corruption in Indonesia - Ericha Cahyo Maryono; Shinta Hadiyantina; Bambang Sugiri (PATTIMURA Legal Journal, 2026)
Introduction: Corruption constitutes an extraordinary crime that causes substantial and real losses to state finances in Indonesia. Despite existing legal mechanisms for substitute money payment execution as stipulated in Article 18 of the Anti-Corruption Law, recovering state losses from corruption remains a critical and persistent challenge. Prosecutors hold a central role in the asset recovery process, functioning not merely as administrative executors of court decisions but also as strategic actors responsible for tracking, seizing, and auctioning convict assets to recover state financial losses. Purposes of the Research: This research investigates why prosecutors, as primary executors of court decisions under Article 18 of the Anti-Corruption Law, face persistent difficulties and obstacles in effective asset recovery. Methods of the Research: Through normative juridical methodology that focuses on the study of positive legal norms, this research analyzes anti-corruption law, prosecutorial law, and state finance regulations. Results Main Findings of the Research: This study identifies a fundamental gap in the existing legal framework: the lack of explicit and comprehensive legal authorization for follow the money and asset tracing approaches in prosecutorial asset recovery operations. The main findings reveal that the absence of clear legal norms governing these investigative methods significantly undermines the effectiveness of asset recovery from corruption crimes. Empirical obstacles include poor inter-institutional coordination, limited access to financial information and banking data, and absent cross-jurisdictional tracking frameworks that hinder comprehensive asset identification. These structural deficiencies reduce asset recovery efforts to reactive administrative processes rather than proactive strategic investigations. Therefore, the study recommends urgent legislative intervention to formally authorize and comprehensively regulate prosecutorial application of follow the money and asset tracing methods. This legal reform is expected to provide legal certainty, enhance prosecutorial accountability, and strengthen the overall effectiveness and integrity of corruption eradication efforts in Indonesia.